Horizons and fireflies (and the present time) - Cerqueira, Helena Magon Pedreira de (Revista ARA, 2020)
Starting from the firefly metaphor suggested by Pier Paolo Pasolini, then further discussed by G. Didi-Huberman in Survival of the fireflies, this essay also reflects themes illuminated by Walter Benjamin. In brief dialogue with other authors, the study takes a look at experiences of perception, apprehension and creation of images that may erupt a flash of blindness in the contemporary world.